Mini-Implants Retaining Removable Partial Dentures in Subjects without Posterior Teeth: A 5-Year Prospective Study Comparing the Maxilla and the Mandible - Asja Celebic; Ines Kovacic; Nikola Petricevic; Dario Puljic; Aleksandra Popovac; Sanja Persic Kirsic (Medicina, 2023)
Background and objectives: Long-term studies of clinical outcomes of mini-implants (MDIs) in the first premolar/canine sites retaining a bilateral free-ending removable partial dentures (RPD) in Kennedy class I subjects have not been well documented. The aim was to assess clinical outcomes in a prospective 5-year cohort study comparing the mandible and maxilla. Material and Methods: Participants (n = 92) who received two MDIs each and a new RPD were reviewed after one, three and five years. A total of 71 participants (82 mini-implants in the mandible; 58 in the maxilla) completed the study. Marginal bone level change, success, survival rates, Modified Plaque (MPI) and Bleeding Indices (MBI) were assessed. Results: The five-year success rate was 93.3% and 93.4% (p > 0.05), in the mandible and the maxilla, respectively. Mean peri-implant bone loss (MBL) increased significantly over five years (p < 0.01) to 0.50 mm in the mandible and 0.52 mm in the maxilla. Age had a significant effect on the MBL (higher rates in younger participants), while jaw of insertion, gender, and antagonistic jaw status did not. MPI and MBI were not significantly correlated with MBL. Conclusions: The insertion of two MDIs in previous first premolar/canine sites for retention of a free-end saddle RPD can be a successful treatment modality in subjects with narrow alveolar ridges.